Pemanfaatan Kecerdasan Buatan dalam Transformasi Intelejen Bisnis untuk Keunggulan Kompetitif - Rini Wijayaningsih; Najwa Andini; Refalina Indah Lestary; Andi Icha Halifah Rahma; Nasywa Tazqiya Ramadani; Jenio Prawirodinata; Zidan Fadliansyah; Yusuf Rahman Maulana (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the impact of artificial intelligence (AI) on business transformation in the digital era. AI has been widely used in various fields such as manufacturing, economy, education, services, finance, and marketing. This article reviews both the positive and negative impacts of AI, as well as the challenges and barriers in its implementation. Using qualitative research methods and case studies, this study identifies the benefits and advantages of AI and provides recommendations for companies in integrating AI into their business processes.